Total Phenolic Content (TPC) and Antioxidant Activities (AOA) of Orange (Citrus Sinensis) and Lemon (Citrus Limon) Peels Extract on Shelf Life of Handmade Donut - HISHAMUDDIN, SHAHMI DANIAL; Razali, Nor Faizah (Progress in Engineering Application and Technology, 2025)
Citrus fruits, especially oranges (Citrus sinensis) and lemons (Citrus limon), are commonly consumed, leading to significant waste in the form of peels. These peels are abundant in bioactive components, including as phenolic acids and flavonoids, which exhibit considerable antioxidant and antibacterial activities. This study examines the efficacy of orange peel extracts as natural antioxidants and food preservatives, providing an environmentally sustainable alternative to synthetic preservatives such as butylated hydroxyanisole (BHA). Citrus peels were subjected to Ultrasonic Assisted Extraction (UAE) utilising ethanol as the solvent to extract phenolic chemicals. The total phenolic content (TPC) and antioxidant activity of the extracts were assessed using the Folin-Ciocalteu method and the DPPH radical scavenging assay, respectively. The findings indicated that lemon peels demonstrated superior total phenolic content (7.564 mg GAE/g) and antioxidant activity (75.79% inhibition) relative to orange peels, which had a total phenolic content of 4.764 mg GAE/g and 67.72% inhibition. The extracts were subsequently put to handmade doughnuts to assess their efficacy as natural preservatives. Lemon peel extracts prolonged the shelf life of the doughnuts to eight days, whilst orange peel extracts extended it to seven days, in contrast to six days for the control sample. BHA, a synthetic preservative, prolonged the shelf life to nine days. Although the antimicrobial test provided no significant results, the data support the use of citrus peel extracts as natural antioxidants and preservatives. This study emphasises the need of converting citrus waste into functional food additives while also addressing environmental issues and developing sustainable food business practices.